Нейтроны цөмийн харилцан үйлчлэлийн судалгааны хөгжил - Г, Хүүхэнхүү; М, Одсүрэн (Scientific transaction of the National University of Mongolia. Physics, 2022)
Origin and development in Mongolia of the study on interaction of neutrons with nuclei in cooperation with the Joint Institute for Nuclear Research are described. New results оf the statistical model analysis for fast neutron induced (n,p) reaction cross sections arc given.